International Conference On Sustainability Engineering Education - Putra Jaya, Ramadhansyah (AIP Publishing, 2024)
With great pleasure we are introducing the International Conference on Sustainability Engineering Education (ICSEE) 2023, yet another series of rewarding conference this year. This conference was organized by Association for Researcher of Skills and Vocational Training (ARSVOT), Malaysia with the support from Institute of Metallurgy and Ore Beneficiation, Satbayev University, Kazakhstan, Department of Mechanical Engineering, Universitas Negeri Padang, Indonesia, Suleyman Demirel University, Kazakhstan and Todox Digital Network, Malaysia. International Conference on Sustainability Engineering Education which was held at the Corus Hotel Kuala Lumpur City Centre, Malaysia on the 24th and 25th June 2023.